2011
DOI: 10.1086/661551
|View full text |Cite
|
Sign up to set email alerts
|

Influence via Comparison-Driven Self-Evaluation and Restoration: The Case of the Low-Status Influencer

Abstract: Ample research shows that consumers accept influence from a source they identify with and reject influence from a source they wish to dissociate from. The current article moves beyond the well-established identification principle and delineates a new influence process. Influence via comparison-driven self-evaluation and restoration (CDSER) takes place when one observes a counterstereotypical product user and, as a result, questions one’s relative standing on the trait that the product symbolizes. In response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 75 publications
(74 reference statements)
5
35
1
Order By: Relevance
“…Whereas prior work has suggested that associative responses to a counterstereotypical person can be driven by an individual-level response (Shalev and Morwitz 2012), we demonstrate conditions under which information regarding the behaviors of a dissociative out-group as a whole can activate a group-level response that drives associative behaviors. Indeed, individual-level motives do not seem to play a role in our context given that a self-affirmation task did not attenuate the effects (Study 2) and individual image motives did not mediate our effects (Study 3).…”
Section: Theoretical Implicationscontrasting
confidence: 78%
See 1 more Smart Citation
“…Whereas prior work has suggested that associative responses to a counterstereotypical person can be driven by an individual-level response (Shalev and Morwitz 2012), we demonstrate conditions under which information regarding the behaviors of a dissociative out-group as a whole can activate a group-level response that drives associative behaviors. Indeed, individual-level motives do not seem to play a role in our context given that a self-affirmation task did not attenuate the effects (Study 2) and individual image motives did not mediate our effects (Study 3).…”
Section: Theoretical Implicationscontrasting
confidence: 78%
“…We achieve the latter by demonstrating that the process underlying the effects is such that comparative concerns lead to the activation of group image motives, which then influence positive intentions to engage in the behavior (Study 3). This is an important contribution to the literature because although prior work has suggested that associative attitudes toward a counterstereotypical person can be driven by an individual-level response (Shalev and Morwitz 2012), we demonstrate conditions under which information regarding the behaviors of a dissociative out-group can activate a group-level response that drives associative individual responses. In addition, we contribute to the reference group literature stream by revealing situations in which image management concerns can lead consumers to act in congruence with a dissociative reference group, whereas previous research has shown only that image management concerns can lead to avoidant responses in relation to the behaviors of dissociative out-groups (Berger and Heath 2007;Dahl 2006, 2007).…”
Section: The Current Researchmentioning
confidence: 68%
“…Theoretically, this research contributes to the growing body of literature that suggests out‐groups or dissociative groups, which have typically been observed to negatively impact consumers’ behaviors (Berger & Heath, , ; Escalas & Bettman, ; White & Dahl, , ), may actually positively impact consumers’ behavior (Choi & Winterich, ; Park & Lee, ; Shalev & Morwitz, ; White et al., ). Specifically, reception of positive benefits (Park & Lee, ), salience of moral identity (Choi & Winterich, ), need for information (Shalev & Morwitz, ), and publicized prosocial behavior (White et al., ) are all factors that have been shown to influence consumers’ decisions to behave in a manner consistent with an out‐group. The findings from Study 2 contribute to this growing body of research by demonstrating that while consumers will initially be more curious about content posted by a membership group, if susceptibility to interpersonal influence is strong enough, content posted by a dissociative group member can also arouse curiosity.…”
Section: Discussionmentioning
confidence: 77%
“…Park and Lee () also find that intentions to donate to a dissociative group increase when consumers perceive that they will receive a benefit. Further, Shalev and Morwitz () find that individuals who are more likely to compare themselves with others demonstrate higher purchase intentions toward products used by dissociative group members than individuals who are less likely to compare themselves to others. They propose that this may be because these individuals are also more likely to question their knowledge, thus exposing a potential information gap.…”
Section: Mediating Role Of Curiositymentioning
confidence: 99%
“…In consumer research, impression management is often discussed in terms of individual responses to social comparison. Recently, consumer researchers have been specifically focusing on threats to one's sense of self (Gao, Wheeler and Shiv, 2009) and how the individual copes with these threat's to one's identity via consumption (Kim and Rucker, 2012;Shalev and Morwitz, 2012). Swann (1987) described this impression management as a process of self-verification.…”
Section: Literature Reviewmentioning
confidence: 99%